2016
DOI: 10.3847/0004-637x/830/2/142
|View full text |Cite
|
Sign up to set email alerts
|

RISING FROM THE ASHES: MID-INFRARED RE-BRIGHTENING OF THE IMPOSTOR SN 2010da IN NGC 300

Abstract: We present multi-epoch mid-infrared (IR) photometry and the optical discovery observations of the "impostor" supernova (SN) 2010da in NGC300 using new and archival Spitzer Space Telescope images and ground-based observatories. The mid-infrared counterpart of SN2010da was detected as Spitzer Infrared Intensive Transient Survey (SPIRITS)14bme in the SPIRITS, an ongoing systematic search for IR transients. Before erupting on 2010 May 24, the SN2010da progenitor exhibited a constant mid-IR flux at 3.6 and only… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
2
21
0
Order By: Relevance
“…Remarkably, the equilibrium temperature radius of surrounding dust (~-R 10 20 au eq ) matches the inner edge radii of spatially resolved galactic sgB[e] disks: 30 au for CPD-52 9243 (Cidale et al 2012) and~-20 30 au for MWC 300 (Wang et al 2012). X-1 is therefore a member of an emerging class of luminous X-ray sources with donor stars that resemble sgB[e] stars such as IGR J16318-4848 (Filliatre & Chaty 2004), GX 301-2 (Servillat et al 2014), and SN2010 da (Binder et al 2016;Lau et al 2016;Villar et al 2016). We note that a majority of known sgB[e] stars do not exhibit significant photometric or spectroscopic variability (e.g., Zickgraf et al 1986); however, there are some sgB[e]s where significant photometric IR variability has been observed, such as CI Cam (Thureau et al 2009) and SN2010 da, both of which are HMXBs.…”
Section: X-1 Donor: a Supergiant B[e] Star?mentioning
confidence: 99%
“…Remarkably, the equilibrium temperature radius of surrounding dust (~-R 10 20 au eq ) matches the inner edge radii of spatially resolved galactic sgB[e] disks: 30 au for CPD-52 9243 (Cidale et al 2012) and~-20 30 au for MWC 300 (Wang et al 2012). X-1 is therefore a member of an emerging class of luminous X-ray sources with donor stars that resemble sgB[e] stars such as IGR J16318-4848 (Filliatre & Chaty 2004), GX 301-2 (Servillat et al 2014), and SN2010 da (Binder et al 2016;Lau et al 2016;Villar et al 2016). We note that a majority of known sgB[e] stars do not exhibit significant photometric or spectroscopic variability (e.g., Zickgraf et al 1986); however, there are some sgB[e]s where significant photometric IR variability has been observed, such as CI Cam (Thureau et al 2009) and SN2010 da, both of which are HMXBs.…”
Section: X-1 Donor: a Supergiant B[e] Star?mentioning
confidence: 99%
“…It was additionally noted during this time that the X-ray energetics favored a highly eccentric binary orbit (e > 0.82; [9]), consistent with the young age inferred from the spectral population synthesis modeling of young stars in the vicinity of the SN 2010da system [23]. Although mid-IR observations of the progenitor yielded firm photometric detections, no X-ray source was detected in pre-2010 archival XMM-Newton observations down to a limiting luminosity of L X < (3 − 9) × 10 36 erg s −1 [22].…”
Section: Sn 2010da As a High Mass X-ray Binarymentioning
confidence: 86%
“…New Chandra and Hubble Space Telescope imaging obtained in 2014 [23] revealed a variable X-ray source coincident with the spatial position of SN 2010da and a bright, blue optical source consistent with a blue supergiant or LBV-like star (shown in Figure 4); the prevalence of young stars in the vicinity of SN 2010da suggests the system has an age of ≤ 5 Myr from population synthesis modeling. Lau et al [9] presented detailed IR SED modeling of the SN 2010da progenitor and progeny, which indicated that a large fraction of the dust that initially enshrouded the SN 2010da progenitor was destroyed during the 2010 outburst. The relatively blue color of the 2010 outburst compared to other SN impostors was noted by Bond [6], and low reddening in 2014 (A V ∼ 0.4 mag) was also inferred from stellar population synthesis modeling in Binder et al [23].…”
Section: Sn 2010da As a High Mass X-ray Binarymentioning
confidence: 99%
“…Very young HMXBs may have substantially different counterparts, for example the supernova impostor SN 2010da has an age of <5 Myr, and it's quite unclear what the donor star is (Lau et al 2016). Our recent Gemini spectroscopy appears that it may be in a transition state, as it exhibits both Be-SG and LBV behavior.…”
Section: Discussionmentioning
confidence: 99%